2019
DOI: 10.1002/smll.201900015
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Buffering Strategy to Boost the Lithium Storage of Botryoid MnOx/C Anodes

Abstract: Small 2019, 15, 1900015 Li/Li + . Electrochemical impedance spectra (EIS) were collected over the frequency range from 0.01 Hz to 100 kHz on an electrochemical workstation (CHI760E). Cyclic voltammetry (CV) was performed at a scan rate of 0.1 mV s −1 within the potential range of 0.01-3.0 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 63 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…Therefore, considerable research efforts have been recently devoted to the development of the derivatives of MOF nanofibers to overcome these limitations. [97] Copyright 2019, Wiley-VCH. A complete and detailed coverage of all the preparation routes, properties, and potential of MOF-nanofiber derivatives in energy applications is exceeding the scope of this review.…”
Section: Preparation Of the Derivatives Of Mof Nanofibersmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, considerable research efforts have been recently devoted to the development of the derivatives of MOF nanofibers to overcome these limitations. [97] Copyright 2019, Wiley-VCH. A complete and detailed coverage of all the preparation routes, properties, and potential of MOF-nanofiber derivatives in energy applications is exceeding the scope of this review.…”
Section: Preparation Of the Derivatives Of Mof Nanofibersmentioning
confidence: 99%
“…For further information, we refer the reader to a recent review dedicated to this topic by the group of Yamauchi. Yang et al [97] reported the fabrication of yolk-shell MnO x nanoparticles confined in carbonized nanofibers (ysMnO x @NC) for use as anode materials in lithium-ion batteries (LIB) (Figure 6b). Interestingly, major changes in the MOF Adv.…”
Section: Preparation Of the Derivatives Of Mof Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the introduction of MOF framework into SnO 2 system by electrospinning and heat treatment to form SnO 2 -M x O y porous nanofibers, many reports have focused on the formation of metal oxide/carbon nanofibers composites formed by co-electrospinning of MOF nanoparticles and polymer and the subsequent heat treatment as electrode materials for batteries. Yang et al have reported a yolk–shell MnOx carbon nanofiber composite (ysMnOx@NC) based on Mn-MOF [72]. The yolk–shell structure of the material can be seen from the Figure 5d.…”
Section: Electrospun Mofs-derived Carbon Nanofibersmentioning
confidence: 99%